Seedling Guard: Assessing Salinity, Nutrient Imbalance, and Temperature Stress on Eggplant Germination in Bogo City - Palermo, Eutequio III Zante L.; Amar, Claire P.; Colis, Jr., Bert P.; Muit, Lhian S. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose – This study investigates the effects of abiotic stress on Long Purple Eggplant seedling germination, specifically temperature, salinity, and nutritional stress. The results are used as a basis for developing an IOT-based and/or embedded systems solution. Method – Investigate the three abiotic stressors: salinity, nutritional imbalance, and temperature extremes. These stressors were chosen because they were repeatedly identified as frequent and visible difficulties in the area. A follow-up interview was used to validate the impact of abiotic stress on seedling development. Use of a Likert scale survey and follow-up interviews with local smallholder farmers. Results – Smart seedling monitoring systems provide real-time monitoring of environmental factors such as temperature, salinity, and soil moisture, which benefits smallholding farmers. This allows for the early detection of stressors, which improves seedling monitoring and production during germination. Using sensors and data analytics, this strategy offers a cost-effective alternative that farmers with limited resources can implement. Finally, implementing this technology improves seedling management, increasing agricultural resilience and sustainability. Conclusion – Abiotic stressors such as heat, salinity, and soil nitrogen imbalance have a major impact on smallholder farmers. These factors interact and impede seedling growth. Local soil management techniques may need to be improved to counterbalance them. Thus, incorporating automated monitoring and management with IoT is a feasible approach for addressing and mitigating these issues in smallholder farming. Recommendations – Employ automated blind features, smart watering, and real-time information to help farmers reduce stress and promote sustainable seedling development in smallholder farming.  Research Implications – This study exhibits more possibilities for exploring other types of seedling germination to be applied with IOT-based and/or embedded systems